The Economic Impact of Clostridium difficile Infection: A Systematic Review. (April 2015) - Nanwa, Natasha; Kendzerska, Tetyana; Krahn, Murray; Kwong, Jeffrey C; Daneman, Nick; Witteman, William; Mittmann, Nicole; Cadarette, Suzanne M; Rosella, Laura; Sander, Beate
Abstract : Objectives: With Clostridium difficile infection (CDI) on the rise, knowledge of the current economic burden of CDI can inform decisions on interventions related to CDI. We systematically reviewed CDI cost‐of‐illness (COI) studies. Methods: We performed literature searches in six databases: MEDLINE, Embase, the Health Technology Assessment Database, the National Health Service Economic Evaluation Database, the Cost‐Effectiveness Analysis Registry, and EconLit. We also searched gray literature and conducted reference list searches. Two reviewers screened articles independently. One reviewer abstracted data and assessed quality using a modified guideline for economic evaluations. The second reviewer validated the abstraction and assessment. Results: We identified 45 COI studies between 1988 and June 2014. Most (84%) of the studies were from the United States, calculating costs of hospital stays (87%), and focusing on direct costs (100%). Attributable mean CDI costs ranged from $8, 911 to $30, 049 for hospitalized patients. Few studies stated resource quantification methods (0%), an epidemiological approach (0%), or a justified study perspective (16%) in their cost analyses. In addition, few studies conducted sensitivity analyses (7%). Conclusions: Forty‐five COI studies quantified and confirmed the economic impact of CDI. Costing methods across studies were heterogeneous. Future studies should follow standard COI methodology, expand study perspectives (e.g., patient), and explore populations least studied (e.g., community‐acquired CDI).